In Vitro and In Vivo Antigen Presentation and Diagnosis Development of Recombinant Overlapping Peptides Corresponding to Mtb ESAT-6/CFP-10 - Zhang, Qing; Lu, Xiong; Gao, Liang; Tao, Siyu; Ge, Yinghua; Cui, Daocheng; Zhu, Renying; Lu, Wenshu; Wang, Jian; Jiang, Shisong (Frontiers in Immunology, 2022)
Cellular immunity in Mycobacteria tuberculosis (Mtb) infection is important for the pathogenesis and final clearance of intracellular Mtb infection. In addition, it is valuable for the diagnosis of tuberculosis. In this pioneering work, we tested in vitro and in vivo antigen presentation and diagnostic application of a recombinant overlapping peptide-protein derived from two Mtb RD1 antigens ESAT-6 and CFP-10 (ROP-TB). The overlapping peptide sequence of ROP-TB is cleaved by the cathepsin S enzyme and covers the entire length of the two proteins. ROP-TB can be expressed and purified from E. coli. Once taken in by antigen-presenting cells, ROP-TB can be cleaved into a peptide pool by cathepsin S within the cells. We found that in dendritic cells, ROP-TB can be processed in 6 hours of co-culture, while the ESAT-6/CFP-10 fusion protein remained in the endosomal compartment. In Mtb-infected mice, ROP-TB stimulated stronger specific T cell responses than pooled synthetic peptides derived from ESAT-6 and CFP-10. With regard to the presentation of in vivo antigens, in a guinea pig model infected with Mtb, ROP-TB induced delayed type hypersensitivity (DTH) responses comparable to those of the tuberculin purified protein derivative (PPD) and ESAT-6/CFP-10 fusion protein. In Mycobacterium bovis (Bovine TB)-infected cattle, ROP-TB elicited DTH responses. Finally, in Mtb infected patients, ROP-TB stimulated cellular immune responses in majority of patients (16/18) of different HLA phenotypes while a single peptide derived from the same proteins did not elicit the immune responses in all patients. In summary, in vitro and in vivo data suggest that ROP-TB stimulates a strong cellular immune response irrespective of HLA phenotypes and is therefore suitable for use in vitro and in vivo diagnostics.